The Influence of Money Supply, Interest Rates, Household Consumption on Inflation in Indonesia - Fitrianti, Mutiara; Rachmawati, Lucky (Jurnal Ekonomika : INDEPENDEN, 2024)
The phenomenon of inflation still often occurs in developing countries such as Indonesia. The inflation rate in Indonesia experiences fluctuating conditions. The inflation problem in Indonesia is caused by many factors. One of them is increasing the amount of money in circulation. This research aims to analyze the influence of the money supply, interest rates and household consumption on the inflation rate in Indonesia in 2009-2022. Using the multiple linear regression analysis method, the results show that 2 independent variables have a positive and significant effect on inflation in 2009-2022, namely the interest rate and household consumption variables. Meanwhile, the money supply variable does not have a significant effect on inflation in Indonesia.